History of Construction of Artificial Irrigation Networks in Mirzachul - Abdurasul Boltaev (Zien Journals, 2024)
As we study the history of Mirzachul, the launch of various irrigation networks, canals, water reservoirs, etc., became extremely important for its irrigation and development. V. I. Masalsky in his work "Land of Turkistan" published in 1913, he said: "During our rule in Central Asia, we did a lot of work in the country, but as fate would have it, we did not do anything in the area of the country's main need, that is, in the area of appropriating new lands, regulating the use of water by law, and increasing the cultivated areas. Despite the great importance of irrigation in Central Asia, we have done almost nothing in Turkestan, except for the work done by the state to irrigate the Murgob rivers and the fact that Romanov irrigated several thousand acres of land. is lying down"1
Keywords: Water; use; irrigation; networks